Kitchen grinder: a tool for the synthesis of metal-organic frameworks towards size selective dye adsorption - Samal, Mahalaxmi; Panda, Jagannath; Biswal, Bishnu P.; Sahu, Rojalin (Crystengcomm, 2018)
In this report, we present a simple, swift mechanochemical synthesis of metal-organic frameworks (MOFs) using a kitchen grinder. By adopting this tool, we could synthesize ZIF-8, CuBTC, and MIL-100(Fe) in multi gram-scale and successfully employ MIL-100(Fe)-KG for the efficient (ca. 98%) removal of an organic dye (methylene blue) from aqueous solution. In particular, we demonstrated the significance of pore aperture for effective dye adsorption by comparing the adsorption behaviours of ZIF-8-KG and MIL-100(Fe)-KG. We believe that this approach could be of economic interest towards the green synthesis of porous adsorbents for waste-water treatment.